An Angel for Christmas - Shekter, Mark.; GoodTimes Home Video (Firm); Blye Migicovsky Productions; Phoenix Animation Studios (New York, NY : GoodTimes Home Video, 2003)
In Ironville, wealthy mill-owner D.D. Kovet has a monopoly on everything, including Christmas! The holiday is against the law as long as he controls things. But when a charming orphan girl named Angela appears in the village square selling her holly sprigs, the entire town is enchanted by this mysterious stranger and her magical wolf companion.
new dvd 2024 fall.
Original songs & lyrics by Mark Shekter.
DVD.
Keywords: Animated films; Children; Children's films; DVD-Video discs; Video recordings; Animated films; Christmas fiction